Translating Psychedelic Therapies From Clinical Trials to Community Clinics: Building Bridges and Addressing Potential Challenges Ahead - Martin L. Williams (Frontiers Media S.A., 2021)
Research exploring the potential of psychedelic-assisted therapies to treat a range of mental illnesses is flourishing, after the problematic sociopolitical history of psychedelics led to the shutdown of clinical research for almost 40 years. Encouraged by positive results, clinicians and patients are now hopeful that further interruptions to research will be avoided, so that the early promise of these therapies might be fulfilled. At this early stage of renewed interest, researchers are understandably focusing more on clinical trials to investigate safety and efficacy, than on longer-term goals such as progression to community practice. Looking to identify and avoid potential pitfalls on the path to community clinics, the authors, a group of Australian clinicians and researchers, met to discuss possible obstacles. Five broad categories of challenge were identified: 1) inherent risks; 2) poor clinical practice; 3) inadequate infrastructure; 4) problematic perceptions; and 5) divisive relationships and fractionation of the field. Our analysis led us to propose some strategies, including public sector support of research and training to establish best practice and optimize translation, and funding to address issues of equitable access to treatment. Above all, we believe that strategic planning and professional cohesion will be crucial for success. Accordingly, our key recommendation is the establishment of a multidisciplinary advisory body, broadly endorsed and representing all major stakeholders, to guide policy and implementation of psychedelic-assisted therapies in Australia. Although these challenges and strategies are framed within the Australian context, we sense that they may generalize to other parts of the world. Wherever they apply, we believe that anticipation of potential difficulties, and creative responses to address them, will be important to avoid roadblocks in the future and keep the “psychedelic renaissance” on track.